PERAN STRATEGIS KEWIRAUSAHAAN DALAM MENDUKUNG KEBIJAKAN FOUR TRACK STRATEGY DI INDONESIA - P Eko Prasetyo (Optimum: Jurnal Ekonomi dan Pembangunan, 2020)
The purpose of this study is to explain the strategic role in overcoming major development problems. The research method used is a literature review with the main variable entrepreneurial strategic role. The data as empirical evidence in this article is taken from a literature review of relevant research results conducted by the previous author and data from the Global Entrepreneurship Monitor (GEM). The results of research that show a good Four Path Strategy (FTS) policy that is able to improve the quality of the economy, finance, finance and distribution inequality only with a policy strategy that is oriented towards entrepreneurship and innovation that is able to increase industrial capacity. If the policy (FTS) is not entrepreneurial oriented and capacity building, then the policy will be more likely to fail.Â